Accuracy of Early Postoperative Clinical and Ultrasound Examination of Arteriovenous Fistulae to Predict Dialysis Use. Issue 4 (July 2014) - Ferring, Martin; Henderson, John; Wilmink, Teun
Aim: The aim of this article is to assess the accuracy of early clinical and ultrasound (US) examination in terms of predicting arteriovenous fistula (AVF) dialysis use. Methods: Physical and US examination of patent AVF was performed 4 weeks after fistula creation. AVF dialysis use was defined as subsequent use of an AVF for at least six consecutive dialysis sessions with two needles and a blood flow of more than 200 mL/min. Results: Of 119 AVF patent at 4 weeks, 26 (22%) failed. Clinical examination was 96% sensitive for predicting successful dialysis, but only 21% specific for failure. Vein diameter above 5 mm and an arterial end-diastolic velocity above 110 cm/s were the best US predictors for dialysis use. Vein diameter was slightly better than arterial velocity in terms of predicting maturity (sensitivity: 83% vs 67%, specificity: 68% vs 65%). All assessments predicted AVF maturity (positive predictive value: clinical = 81%, US diameter = 90%, US velocity = 87%) much better than AVF failure (negative predictive value: clinical = 63%, US diameter = 53%, US velocity = 37%). Conclusion: One month after surgery, a new AVF with a thrill or a vein diameter >5 mm is likely to be used for dialysis. An AVF not meeting these criteria has an increased risk of failure and further investigations may be required.